Kemampuan Koneksi Matematis Mahasiswa pada Materi Aplikasi Barisan dan Deret dalam Ekonomi dan Bisnis - Sulisti, Hidayu (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to identify the level of mathematical connection skills of students on the application material of rows and series in economics and business, and analyze the factors that influence it. This research is a descriptive research with a survey form. The research subjects were 1st semester students of IAIN Pontianak's Sharia Economics Study Program who had taken the course on the application of arithmetic ranks and series in economics and business.  The procedure in this research consists of 3 stages, namely: 1) Preparation stage, 2) Implementation stage, 3) The final stage. The results of this study indicate that the mathematical connection skills of sharia economics students of IAIN Pontianak on the application material of rows and series in economics and business still need to be improved. Some students were able to answer all the questions correctly, but most were only able to answer some of the questions or none of them were correct. This shows that students' understanding of this material is very diverse. Some factors that may contribute to this result include: learning approach, lack of practice, perception of mathematics, and limited resources. To overcome this problem, various efforts are needed from both lecturers and students. Thus, it is hoped that students can be better prepared to face challenges in the world of work that require critical and analytical thinking skills.